Plan de promoción turística para los talleres artesanales de la comunidad de Peguche cantón de Otavalo, Provincia de Imbabura. - Terán Terán, Paccha Pakarina (2023)
In the province of Imbabura, 15 minutes from the city of Otavalo, is the famous community of Kichwa origin, called Peguche. This site has several tourist attractions. Likewise, it is a land of musicians and artisans, and therefore it has workshops where you can find various textile crafts, which continue to preserve the ancestral techniques for their elaboration, which constitutes a great tourist potential. Currently, tourists do not have extensive knowledge about the workshops, because there has been no further promotion. The purpose of this research work is to value four artisan workshops in the Peguche community, Otavalo Canton, Imbabura Province, through a tourism promotion plan that promotes the arrival of tourists. The applied methodology consisted of surveys and interviews with both local artisans and authorities from the Peguche community. The results found show that the artisans agree to execute a Tourism Promotion Plan for their workshops\; likewise, the authorities mentioned that there is no budget allocated to this type of strategy, however, a web page was created where information can be found on four Peguche artisan workshops. It is concluded that the best strategy to promote the attractions of Peguche are social networks, as well as strategic alliances with the private sector, such as local and national travel agencies